2012
DOI: 10.1371/journal.pone.0038167
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Prodrugs of FR900098 Are Antimicrobial against Francisella novicida In Vivo and In Vitro and Show GlpT Independent Efficacy

Abstract: Bacteria, plants, and algae produce isoprenoids through the methylerythritol phosphate (MEP) pathway, an attractive pathway for antimicrobial drug development as it is present in prokaryotes and some lower eukaryotes but absent from human cells. The first committed step of the MEP pathway is catalyzed by 1-deoxy-D-xylulose 5-phosphate reductoisomerase (DXR/MEP synthase). MEP pathway genes have been identified in many biothreat agents, including Francisella, Brucella, Bacillus, Burkholderia, and Yersinia. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 48 publications
(111 reference statements)
1
76
0
Order By: Relevance
“…These limitations have led to substantial efforts to develop more cell-permeable analogs of FSM or its highly related analog FR900098 (30)(31)(32)(33)(34)(35). Because many FSM derivatives are prodrugs that require intracellular activation, it is often impossible to test the efficacy of these compounds directly on the Dxr target enzyme in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations have led to substantial efforts to develop more cell-permeable analogs of FSM or its highly related analog FR900098 (30)(31)(32)(33)(34)(35). Because many FSM derivatives are prodrugs that require intracellular activation, it is often impossible to test the efficacy of these compounds directly on the Dxr target enzyme in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this impermeability, FSM is ineffective against many potential pathogens, such as Toxoplasma gondii (29) and M. tuberculosis (10). Thus, substantial efforts have been made to develop more cell-permeable analogs of FSM or its highly related analog, FR900098 (30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…[23][24][25][26] Using these techniques to develop a phenotypic screen, we identified compounds from the FDAapproved drug library that exerted antibiofilm (but not antimicrobial) activity against F. novicida. More clearly, we defined antibiofilm activity as inhibition of bacterial biofilm formation to a significantly greater amount than inhibition of bacterial growth (cutoff of 50% for growth inhibition).…”
Section: Screen a Fda-approved Drug Librarymentioning
confidence: 99%
“…24,26,43 To evaluate the ability of selected drugs to prolong survival of infected G. mellonella, larvae were inoculated with 10 mL of PBS containing a lethal dose of F. novicida and treated with selected drugs. We found that the polycyclic compounds maprotiline and chlorpromazine and the SERM, toremifene, all significantly prolonged survival in the waxworm model (Fig.…”
Section: Fda-approved Drug Maprotiline Prolongs Survival Of Galleria mentioning
confidence: 99%
See 1 more Smart Citation